A Juridical And Human Factors Analysis Of Civil Aviation Accidents And Incidents Involving Air Traffic Control: A Literature Review Based On Indonesian Aviation Regulations And ICAO Standards - Freshal Fitran; Elfi Amir; Rany Adiliawijaya Putriekapuja (International Journal of Health Engineering and Technology, 2026)
This study analyzes the contribution of legal aspects and human factors to civil aviation accidents and incidents associated with Air Traffic Control (ATC) services. Utilizing a qualitative descriptive literature review methodology, this research conducts a comparative evaluation of the Halim Perdanakusuma runway collision accident (2016) and the Austin-Bergstrom near-miss incident (2023). The juridical framework is anchored in Indonesian Aviation Law No. 1 of 2009 and International Civil Aviation Organization (ICAO) standards, while systemic analysis applies the SHELL model and HFACS taxonomy. The results indicate that expectation bias and operational deviations from standardized radio-telephony phraseology are the primary drivers of cognitive and procedural failures. Weak supervisory monitoring and the absence of integrated surface surveillance technology further compromised the systemic defenses in both cases. In conclusion, runway accidents and incidents do not result from isolated operator errors but stem from interactive mismatches within the sociotechnical system. Enforcing legal compliance with standard safety procedures and accelerating the deployment of surface detection radar are critical mitigation strategies to prevent future occurrences.